The Effect of Drivers and Outcomes of Brand Engagement in Self Concept on Luxury Bag Brand - Indiera Lievea Dewi; Sri Vandayuli Riorini (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze the effect drivers and outcomes of brand engagement in self-concept on luxury bag brands. The primary data collection method used is the questionnaire method with purposive sampling and non-probability sampling techniques to 120 respondents who have luxury branded bags. Data were analyzed using Covariance-Based Structural Equation Modeling (SEM). The results of this study indicate that Social Media Marketing Social media marketing activities positively affect BESC (Brand engagement in self-concept).